Radiocarbon Reveals Modern Carbon Exchange With Topsoil Inorganic Carbon in Drylands - Hui Wang; Jianbei Huang; Fernando T. Maestre; Guang Zhao; Nan Lu; Cong Wang; Weiliang Chen; De Shorn E. Bramble; Marion Schrumpf; Michaela A. Dippold; Yangjian Zhang; Sönke Zaehle; et al. (Global Change Biology, 2026)
Drylands store most of the global soil inorganic carbon (SIC), yet the extent to which this pool interacts with contemporary carbon (C) cycling remains poorly understood. To test whether SIC behaves primarily as an inert geological reservoir or instead bears a modern carbon imprint, we quantified SIC content and radiocarbon (∆ 14 C) at 42 dryland sites spanning broad aridity gradients across Eurasia. We also evaluated the climatic, edaphic, and biotic factors associated with variation in ∆ 14 C‐SIC. Across all sites, topsoil SIC (~0–10 cm) was strongly depleted in 14 C but consistently enriched relative to 14 C‐dead carbonates, indicating that it contains a measurable component derived from modern carbon inputs. In the Chinese drylands, ∆ 14 C‐SIC declined with increasing aridity, consistent with weaker modern carbon exchange under drier conditions and a greater contribution of inherited or 14 C‐depleted carbonate carbon. Soil pH and ∆ 14 C of soil organic carbon were the strongest predictors of ∆ 14 C‐SIC, suggesting that carbonate dissolution‐reprecipitation and the age of carbon entering soil CO 2 play key roles in determining SIC origins. At a subset of nine Chinese sites, ∆ 14 C‐SIC declined sharply with depth and approached 14 C‐dead values in subsoils, indicating little influence of modern carbon in deeper carbonate pools. The presence of mixed 14 C‐depleted and modern 14 C signatures in SIC potentially complicates the use of SIC isotopic signatures as proxies of environmental conditions. Together, our results indicate that dryland topsoil SIC commonly carries a measurable modern carbon signature that is tightly linked to contemporary carbon cycling. This coupling weakens with increasing aridity and soil depth, suggesting that environmental change in drylands may reshape one of the planet's largest carbon pools not only through changes in SIC stocks, but also through shifts in carbonate radiocarbon signatures and sources.

Corrigendum to “Mapping long-term soil organic carbon stocks across the conterminous United States with machine learning” [Environ Res. 306 (2026) 125271] - Hannah J. Rubin; Xinxin Zhang; Joshua S. Fu; T. Edward Yu (Environmental Research, 2026)

Mapping long-term soil organic carbon stocks across the conterminous United States with machine learning - Hannah J. Rubin; Xinxin Zhang; Joshua S. Fu; T. Edward Yu (Environmental Research, 2026)

In situ apatite fission track, UPb and trace elements analysis using LA-ICP-MS - Jianzhang Pang; Jing Yang; Yan Ma; Dewen Zheng; Murat T. Tamer; Ying Wang; Jingxing Yu; Chaopeng Li; Yizhou Wang; Zhijin Fu; Mustafa Kaya; Yuehui An (Journal of Geochemical Exploration, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Investigating Sulfotransferase Mediated Drug Interactions of Ethinylestradiol using a Physiologically Based Pharmacokinetic Model - Harry P. Moore; Kuan-Fu Chen; Aki T. Heikkinen; Sibylle Neuhoff; Udoamaka Ezuruike; Jean Dinh; Iain Gardner; Hannah M. Jones; Felix Stader (The AAPS Journal, 2025)

P30-60 Grouping and assessment of chemicals for hazard and risk assessment by high content analysis using the zebrafish embryos as an alternative non-sentient animal model - S. Scholz; C. Zanini; A.-K. Koblitz; T. Möller; M.A. Aslam; G.C. Ajugwo; E. Chukwu; J. Colbourne; S. Kader; Q. Fu; N. Grasse; T. Reemtsma; et al. (Toxicology Letters, 2025)

P30-57 Towards a Defined Approach to Assess Pesticides for their Potential to Cause Parkinsonian Neurodegeneration - J. Nyffeler; T. Tal; S. Schildknecht; B. Viviani; B. Tanja; Q. Fu; R. Owen; A.E.V. Krishnakumar; I. Mangas; A. Terron (Toxicology Letters, 2025)

P16-05 The zebrafish microbiome has the capacity to bioactivate PFOS precursor compounds - S. Gutsfeld; C. Wray; N. Schweiger; A. Röhrig; H. Paschke; Q. Fu; J. Kasmanas; S. Kader; U. da Rocha; T. Tal (Toxicology Letters, 2025)

White matter microstructural abnormalities related to emotional dysfunction and childhood trauma characterize adolescents with borderline personality disorder - Xiaoping Yi; Xueying Wang; Liying Shen; Yan Fu; Qian Xiao; Jinfan Zhang; Jun Ding; Furong Jiang; Zhejia Zhang; Alessandro Grecucci; Bihong T. Chen (Brain Imaging and Behavior, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Soil and litter microbiomes as joint drivers of ecosystem multifunctionality in a 60-year-old forest plantation - Shu-Yi-Dan Zhou; Xu Li; Josep Peñuelas; David T. Tissue; Roy Neilson; Xujun Liu; Zhiyang Lie; Fu-Yi Huang; Junhua Yan; Dong Zhu; Juxiu Liu (Journal of Environmental Management, 2025)

Comprehensive extractables and leachables sensitization analysis and practical application of a risk-based approach to sensitization assessment for parenteral drug products - Patricia Parris; Geraldine Whelan; Martyn L. Chilton; Claire Beaumont; Anders Burild; Uma Bruen; Courtney Callis; Jessica Graham; Natalia Kovalova; Elizabeth A. Martin; Melisa Masuda-Herrera; Carsten Worsøe; et al. (Regulatory Toxicology and Pharmacology, 2025)

Ammonia inhibition in anaerobic digestion of organic waste: a review - J. Yang; J. Zhang; X. Du; T. Gao; Z. Cheng; W. Fu; S. Wang (International Journal of Environmental Science and Technology, 2025)
Anaerobic digestion (AD) has become the technology of choice for organic waste treatment as an environmentally beneficial and sustainable waste treatment technology. However, the nitrogen content of these organic waste streams is generally high. Ammonia is produced in the biodegradation of nitrogenous organic matter. Low concentrations of ammonia favour AD, but high concentrations can lead to digestive system failure. To address the issue of ammonia inhibition and ensure the stability of the digestive system, numerous physical, chemical, and biologicalmethods aimed at controlling ammonia levels and/or strengthening the biological processes have been proposedand developed. Literature evidence suggests that differences in AD reaction conditions and microbial sources result in different tolerances of the digestive system to ammonia and nitrogen. This paper summarises and compares the inhibitory effects of ammonia nitrogen under different conditions and the existing regulatory measures to alleviate ammonia nitrogen inhibition. In addition, since the core of the digestive system is microorganisms, this paper explains the mechanism of ammonia stress especially at the microbial level, and in this way, it explores the future direction of research using biofortification. This review provides a theoretical reference for solving the problem of ammonia nitrogen inhibition.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Feasibility study of machine learning to explore relationships between antimicrobial resistance and microbial community structure in global wastewater treatment plant sludges - Yi Li; Cuicui Tao; Shuyin Li; Wenxuan Chen; Dafang Fu; Chad T. Jafvert; Tengyi Zhu (Bioresource Technology, 2025)

Acceptability of a Fresh Produce Intervention for Individuals With Serious Mental Illnesses - Gabriella Farland; Leah G. Pope; En Fu; Dana Cohen; Cheryl Gerstler; Merrill Rotter; Michael T. Compton (Journal of Nutrition Education and Behavior, 2025)

From space to street: A systematic review of the associations between visible greenery and bluespace in street view imagery and mental health - Mondira Bardhan; Fu Li; Mathew H.E.M. Browning; Jiaying Dong; Kuiran Zhang; Shuai Yuan; Hüseyin Ertan İnan; Olivia McAnirlin; Dani T. Dagan; Allison Maynard; Katie Thurson; Fan Zhang; et al. (Environmental Research, 2024)

Chemical classification of spherules recovered from the Pacific Ocean site of the CNEOS 2014-01-08 (IM1) bolide - A. Loeb; S.B. Jacobsen; R. Tagle; T. Adamson; S. Bergstrom; J. Cherston; R. Cloete; S. Cohen; L. Domine; H. Fu; C. Hoskinson; E. Hyung; et al. (Chemical Geology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An Expanded National Database for Natural Product Use and Interaction Assessment - Y. Fu; T. Feinberg; E. Dennis (Journal of the Academy of Nutrition and Dietetics, 2024)

Fate of florfenicol and linezolid resistance genes and their bacterial hosts during two waste treatment models in swine feedlots - Zheng Wang; Yulin Fu; Yong-Liang Zheng; Nansong Jiang; Haiyang Jiang; Congming Wu; Ziquan Lv; Henrike Krüger-Haker; Andrea T. Feßler; Stefan Schwarz; Yang Wang (Science of The Total Environment, 2024)

The DECOVALEX international collaboration on modeling of coupled subsurface processes and its contribution to confidence building in radioactive waste disposal - Jens T. Birkholzer; Alexander E. Bond; Chin-Fu Tsang (Hydrogeology Journal, 2024)
The long-lived radiotoxicity of the high-level radioactive waste generated by nuclear power plants requires safe isolation from the biosphere for many hundreds of thousands of years. An international consensus has emerged that such isolation can best be provided by disposal in mined geologic repositories, a strategy that today is pursued by most countries dealing with radioactive waste. However, the need to predict the performance of such repositories over very long time periods generates large uncertainties that have to be accounted for in safety assessments. The findings from such safety assessments need to be conveyed to all stakeholders in a clear way, such that public confidence in geologic disposal solutions can be achieved. It is suggested here that close international collaboration on the technical aspects of geologic waste disposal has helped, and will continue to help, building trust and increasing confidence. This paper discusses a particular international collaboration initiative referred to as DECOVALEX, which brings together multiple teams and disciplines to collectively tackle complex experimental and modeling challenges related to geologic disposal. By describing how DECOVALEX works and by providing joint research examples, a case is made that such international collaboration contributes to knowledge transfer and confidence building in radioactive waste disposal science.

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

Integrating molecular descriptors for enhanced prediction: Shedding light on the potential of pH to model hydrated electron reaction rates for organic compounds - Yi Li; Cuicui Tao; Dafang Fu; Chad T. Jafvert; Tengyi Zhu (Chemosphere, 2024)

Degradation of cathode in air and its influences on direct recycling - Yi Ji; Chad T. Jafvert; Fu Zhao (Journal of Cleaner Production, 2024)

Tree species diversity increases soil microbial carbon use efficiency in a subtropical forest - Pengpeng Duan; Ruitong Fu; Andrew T. Nottingham; Luiz A. Domeignoz‐Horta; Xinyi Yang; Hu Du; Kelin Wang; Dejun Li (Global Change Biology, 2023)
Plant communities strongly influence soil microbial communities and, in turn, soil carbon (C) cycling. Microbial carbon use efficiency (CUE) is an important parameter for predicting soil C accumulation, yet how plant and soil microbial community traits influence microbial CUE remains poorly understood. Here, we determined how soil microbial CUE is influenced by plant and soil microbial community traits, by studying a natural gradient of plant species diversity in a subtropical forest. Our results showed that microbial CUE increased with increasing tree species diversity, suggesting a correlation between plant community traits and soil C storage. The specific soil properties that explained the greatest variation in microbial CUE were associated with microbial communities (biomass, enzyme activities and the ratio of oligotrophic to copiotrophic taxa); there were weaker correlations with plant‐input properties, soil chemistry and soil organic C quality and its mineral protection. Overall, high microbial CUE was associated with soil properties correlated with increased tree species diversity: higher substrate availability (simple SOM chemical structures and weak mineral organic associations) and high microbial growth rates despite increased community dominance by oligotrophic strategists. Our results point to a mechanism by which increased tree species diversity may increase the forest C sink by affecting carbon use with the soil microbial community.

Ophiolites and Earth's mantle ophiolites, podiform chromitites and deep mantle recycling - Paul T. Robinson; Mei-Fu Zhou; Jingsui Yang; Fahui Xiong; Peng-Fei Zhang (Lithos, 2023)

Water content imaging during capillary rise within a rammed earth structure - A. Ghorbani; T. Chitimbo; A. Revil; N. Prime; K. Zhang; T. Fu; O. Plé (Engineering Geology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Ecological sustainability assessment of building glass industry in China based on the point of view of raw material emergy and chemical composition - Junxue Zhang; He Zhang; Ashish T. Asutosh; Nameng Sun; Xiaohui Fu; Hairuo Wang; Xindi Li (Environmental Science and Pollution Research, 2023)

Drylands contribute disproportionately to observed global productivity increases - Shuai Wang; Bojie Fu; Fangli Wei; Shilong Piao; Fernando T. Maestre; Lixin Wang; Wenzhe Jiao; Yanxu Liu; Yan Li; Changjia Li; Wenwu Zhao (Science Bulletin, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Effects of environmental factors on release amount of heavy metal and structure of microbial community in sediments - T. Wen; H. Zhong; G. Fu; Y. Zhong (International Journal of Environmental Science and Technology, 2022)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Translation, ribosome biogenesis, and oxidative damage caused by chlorpyrifos exposure to common carp (Cyprinus carpio L.) liver: application of combined RNA-seq with sRNA-seq in risk evaluation of environmental toxicant chlorpyrifos - Jing Fu; Minghui Wang; Maria T. Chaudhry; Hongfei Xue; Lichun Zhang; Yanhua Huang; Chunpeng Liu (Environmental Science and Pollution Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Use of Microfluidics to Fabricate Bioerodable Lipid Hybrid Nanoparticles Containing Hydromorphone or Ketamine for the Relief of Intractable Pain - Minze Zhu; Andrew K. Whittaker; Xingyu Jiang; Rupei Tang; Xuanyu Li; Weizhi Xu; Changkui Fu; Maree T Smith; Felicity Y Han (Pharmaceutical Research, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Enhanced pyrogallol toxicity to cyanobacterium Microcystis aeruginosa with increasing alkalinity - Yunni Gao; Qinqin Fu; Jing Lu; Hui Yang; Philip T. Orr; Fang Zhang; Jing Dong; Man Zhang; Qianhong Gu; Chuanjiang Zhou; Michele A. Burford (Journal of Applied Phycology, 2020)

The southern Amazon rainy season: The role of deforestation and its interactions with large‐scale mechanisms - Argemiro T. Leite‐Filho; Marcos H. Costa; Rong Fu (International Journal of Climatology, 2020)
Past studies presented evidence that deforestation may affect the precipitation seasonality in southern Amazon. This study uses daily rainfall data from Tropical Rainfall Measurement Mission 3B42 product and a recent yearly 1‐km land use dataset to evaluate the quantitative effects of deforestation on the onset, demise and length of the rainy season in southern Amazon for a period of 15 years (1998–2012). Additionally, we use the Niño4 index, zonal wind data and deforestation data to explain and predict the interannual variability of the onset of the rainy season. During this period, onset has delayed ~0.38 ± 0.05 days per year (5.7 ± 0.75 days in 15 years), demise has advanced 1.34 ± 0.76 days per year (20 ± 11.4 days in 15 years) and the rainy season has shortened by 1.81 ± 0.97 days per year (27 ± 14.5 days in 15 years). Onset, demise and length also present meridional and zonal gradients linked to large‐scale climate mechanisms. After removing the effects related to geographical position and year, we verified a relationship between onset, demise and length and deforestation: Onset delays ~0.4 ± 0.12 day, demise advances ~1.0 ± 0.22 day and length decreases ~0.9 ± 0.34 day per each 10% deforestation increase relative to existing forested area. We also present empirical evidence of the interaction between large‐scale and local‐scale processes, with interannual variation of the onset in the region explained by Niño4 sea surface temperature anomalies, Southern Hemisphere subtropical jet position, deforestation and their interactions ( r 2 = 69%, p

Differential effects of various genetic mouse models of the mechanistic target of rapamycin complex I inhibition on heart failure - Dao-Fu Dai; Yonggang Liu; Nathan Basisty; Pabalu Karunadharma; Somasish G. Dastidar; Ying Ann Chiao; Tony Chen; Richard P. Beyer; Michael T. Chin; Michael Maccoss; Albert R. La Spada; Peter S. Rabinovitch (GeroScience, 2019)

An efficient high-order multiscale finite element method for frequency-domain elastic wave modeling - Shubin Fu; Kai Gao; Richard L. Gibson; Eric T. Chung (Computational Geosciences, 2019)

Global Observations of Fine-Scale Ocean Surface Topography With the Surface Water and Ocean Topography (SWOT) Mission - Rosemary Morrow; Lee-Lueng Fu; Fabrice Ardhuin; Mounir Benkiran; Bertrand Chapron; Emmanuel Cosme; Francesco d’Ovidio; J. Thomas Farrar; Sarah T. Gille; Guillaume Lapeyre; Pierre-Yves Le Traon; Ananda Pascual; et al. (Frontiers in Marine Science, 2019)

Preface: Bioactive substances of various seaweeds and their applications and utilization - Delin Duan; Alan T. Critchley; Xiaoting Fu; Leonel Pereira (Journal of Oceanology and Limnology, 2019)

A Survey Regarding the Knowledge, Attitudes, and Beliefs of Graduates of Cancer Rehabilitation Fellowship Program - Rajesh R. Yadav; An T. Ngo-Huang; Jack B. Fu; Amy Ng; Christian Custodio; Eduardo Bruera (Journal of Cancer Education, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Characteristics of Cancer Rehabilitation Fellowship Training Programs in the USA - Rajesh R. Yadav; An T. Ngo-Huang; Amy Ng; Jack B. Fu; Christian Custodio; Eric Wisotzky; Raj Mitra; Eduardo Bruera (Journal of Cancer Education, 2018)

Improving the knowledge and behavior of workplace chemical exposures in Vietnamese–American nail salon workers: a randomized controlled trial - Thu Quach; J. Von Behren; J. Tsoh; P. Reynolds; L. Fu; T. Nguyen; M. Le; T. T. Nguyen (International Archives of Occupational and Environmental Health, 2018)

Analysis of the Spatial Variation and Identification of Factors Affecting the Water Resources Carrying Capacity Based on the Cloud Model - K. Cheng; Q. Fu; J. Meng; T. X. Li; W. Pei (Water Resources Management, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Flowing fluid electrical conductivity logging of a deep borehole during and following drilling: estimation of transmissivity, water salinity and hydraulic head of conductive zones - Christine Doughty; Chin-Fu Tsang; Jan-Erik Rosberg; Christopher Juhlin; Patrick F. Dobson; Jens T. Birkholzer (Hydrogeology Journal, 2017)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Analysis of 6-year fluid electric conductivity logs to evaluate the hydraulic structure of the deep drill hole at Outokumpu, Finland - Prabhakar Sharma; Chin-Fu Tsang; Ilmo T. Kukkonen; Auli Niemi (International Journal of Earth Sciences, 2016)

Molecular characterization of two divergent variants of sugarcane bacilliform viruses infecting sugarcane in China - Sheng-Ren Sun; Mona B. Damaj; Olufemi J. Alabi; Xiao-Bin Wu; T. Erik Mirkov; Hua-Ying Fu; Ru-Kai Chen; San-Ji Gao (European Journal of Plant Pathology, 2016)

Analyzing Economic and Environmental Performance of Switchgrass Biofuel Supply Chains - T. Edward Yu; Burton C. English; Lixia He; James A. Larson; James Calcagno; Joshua S. Fu; Brad Wilson (BioEnergy Research, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

The role of salinity in seed maturation of the euhalophyte Suaeda salsa - J. C. Zhou; T. T. Fu; N. Sui; J. R. Guo; G. Feng; J. L. Fan; J. Song (Plant Biosystems, 2016)

Calibration and application of an automated seepage meter for monitoring water flow across the sediment-water interface - Tengyi Zhu; Dafang Fu; Byron Jenkinson; Chad T. Jafvert (Environmental Monitoring and Assessment, 2015)

Effect of the invasive bivalve Mytilopsis sallei on the macrofaunal fouling community and the environment of Yundang Lagoon, Xiamen, China - L.-Z. Cai; J.-S. Hwang; H.-U. Dahms; S.-J. Fu; Y. Zhuo; T. Guo (Hydrobiologia, 2014)

Assessing scalar concentration footprint climatology and land surface impacts on tall-tower CO2 concentration measurements in the boreal forest of central Saskatchewan, Canada - Baozhang Chen; Huifang Zhang; Nicholas C. Coops; Dongjie Fu; Douglas E. J. Worthy; Guang Xu; T. Andy Black (Theoretical and Applied Climatology, 2014)

Eukaryotic elongation factor-2 kinase (eEF2K): a potential therapeutic target in cancer - L. L. Fu; T. Xie; S. Y. Zhang; B. Liu (Apoptosis, 2014)

Genome characterization of sugarcane yellow leaf virus from China reveals a novel recombinant genotype - Yi-Hua Lin; San-Ji Gao; Mona B. Damaj; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov (Archives of Virology, 2014)

Comparative genotype reactions to Sclerotinia sclerotiorum within breeding populations of Brassica napus and B. juncea from India and China - M. J. Barbetti; S. K. Banga; T. D. Fu; Y. C. Li; D. Singh; S. Y. Liu; X. T. Ge; S. S. Banga (Euphytica, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

An analysis of the drought and flood hazard characteristics and risks during the pre-rainy season in South China - L. P. Li; K. M. Zhang; T. Luo; Xiouhua Fu (Natural Hazards, 2014)

Histone deacetylase inhibitor AR-42 enhances E7-specific CD8+ T cell-mediated antitumor immunity induced by therapeutic HPV DNA vaccination - Sung Yong Lee; Zhuomin Huang; Tae Heung Kang; Ruey-Shyang Soong; Jayne Knoff; Ellen Axenfeld; Chenguang Wang; Ronald D. Alvarez; Ching-Shih Chen; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Origin of the Tongbai-Dabie-Sulu Neoproterozoic low-δ 18O igneous province, east-central China - Bin Fu; Noriko T. Kita; Simon A. Wilde; Xiaochun Liu; John Cliff; Alan Greig (Contributions to Mineralogy and Petrology, 2013)

Differentiation, crustal contamination and emplacement of magmas in the formation of the Nantianwan mafic intrusion of the ~260 Ma Emeishan large igneous province, SW China - Christina Yan Wang; Mei-Fu Zhou; Yali Sun; Nicholas T. Arndt (Contributions to Mineralogy and Petrology, 2012)

Apigenin Attenuates Insulin-Like Growth Factor-I Signaling in an Autochthonous Mouse Prostate Cancer Model - Sanjeev Shukla; Gregory T. MacLennan; Pingfu Fu; Sanjay Gupta (Pharmaceutical Research, 2012)

The effect of using inconsistent ocean tidal loading models on GPS coordinate solutions - Yuning Fu; Jeffrey T. Freymueller; Tonie van Dam (Journal of Geodesy, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

Heterogeneous mantle source and magma differentiation of quaternary arc-like volcanic rocks from Tengchong, SE margin of the Tibetan Plateau - Mei-Fu Zhou; Paul T. Robinson; Christina Yan Wang; Jun-Hong Zhao; Dan-Ping Yan; Jian-Feng Gao; John Malpas (Contributions to Mineralogy and Petrology, 2012)

Constraining the mid-crustal channel flow beneath the Tibetan Plateau: data from the Nielaxiongbo gneiss dome, SE Tibet - Dan-Ping Yan; Mei-Fu Zhou; Paul T. Robinson; Djordje Grujic; John Malpas; Allen Kennedy; Peter H. Reynolds (International Geology Review, 2012)

d-amino acids for the enhancement of a binary biocide cocktail consisting of THPS and EDDS against an SRB biofilm - D. Xu; J. Wen; W. Fu; T. Gu; I. Raad (World Journal of Microbiology and Biotechnology, 2012)

Molecular cloning, characterization and expression analysis of B cell translocation gene 1 in grass carp Ctenopharyngodon idella - Y. J. Fu; F. G. Huang; T. Yuan; J. R. Gu; G. Q. Luo; H. Xu (Journal of Fish Biology, 2012)
An expressed sequence tag (EST) of B cell translocation gene (BTG) 1 ( gcbtg1 ) was obtained from a grass carp Ctenopharyngodon idellus intestinal complementary (c)DNA library and the full‐length cDNA sequence was acquired by rapid amplification of cDNA ends (RACE) technology. The predicted Gcbtg1 protein contains the box A and box B motifs which characterized the BTG and transducer of ERBB2 (TOB) family. Multiple alignment analysis reveals that Gcbtg1 shares an overall identity of 65–94% with Gcbtg1s of other vertebrates. Real‐time quantitative PCR analysis reveals that the highest expression level of gcbtg1 was detected in liver and the lowest in muscle. Western blotting analysis indicates that the immunological cross‐reactivity occurs between C. idella and human Homo sapiens BTG1 protein. A 1008 bp 5′‐flanking region sequence was cloned and analysed.

Late Triassic bivalves associated with a hydrothermal vent system in the Yidun Island Arc (SW China) of the eastern Tethys - Li Lin; LiDong Zhu; YanChun Pang; JinGeng Sha; Franz T. Fürsich; XiuGen Fu; XinLi Wang (Science China Earth Sciences, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Differential distribution of heparan sulfate glycoforms and elevated expression of heparan sulfate biosynthetic enzyme genes in the brain of mucopolysaccharidosis IIIB mice - Douglas M. McCarty; Julianne DiRosario; Kadra Gulaid; Smruti Killedar; Arie Oosterhof; Toin H. van Kuppevelt; Paul T. Martin; Haiyan Fu (Metabolic Brain Disease, 2011)

Reply to Comments by Veling on “A Semi-Analytical Solution for Large-Scale Injection-Induced Pressure Perturbation and Leakage in a Laterally Bounded Aquifer–Aquitard System” by Zhou, Birkholzer, and Tsang - Quanlin Zhou; Jens T. Birkholzer; Chin-Fu Tsang (Transport in Porous Media, 2011)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

OSTM/Jason-2: Assessment of the System Performances (Ocean Surface Topography Mission: OSTM) - G. Zaouche; J. Perbos; T. Lafon; V. Couderc; J. Lambin; J. D. Desjonqueres; C. Jayles; E. Jurado; P. Vaze; L.-L. Fu; S. Brown; F. Parisot; et al. (Marine Geodesy, 2010)

How are seasonal prediction skills related to models’ performance on mean state and annual cycle? - June-Yi Lee; Bin Wang; I.-S. Kang; J. Shukla; A. Kumar; J.-S. Kug; J. K. E. Schemm; J.-J. Luo; T. Yamagata; X. Fu; O. Alves; B. Stern; et al. (Climate Dynamics, 2010)

Therapeutic HPV DNA vaccines - Ken Lin; Elena Roosinovich; Barbara Ma; Chien-Fu Hung; T.-C. Wu (Immunologic Research, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

Multiple origins of zircons in jadeitite - Bin Fu; John W. Valley; Noriko T. Kita; Michael J. Spicuzza; Chad Paton; Tatsuki Tsujimori; Michael Bröcker; George E. Harlow (Contributions to Mineralogy and Petrology, 2010)

Epigenetic regulation of peanut allergen gene Ara h 3 in developing embryos - Guohua Fu; Yujuan Zhong; Chenlong Li; Yin Li; Xiaodong Lin; Bin Liao; Edward W. T. Tsang; Keqiang Wu; Shangzhi Huang (Planta, 2010)

Impacts of cascade run-of-river dams on benthic diatoms in the Xiangxi River, China - N. Wu; T. Tang; X. Fu; W. Jiang; F. Li; S. Zhou; Q. Cai; N. Fohrer (Aquatic Sciences, 2010)

Co-localization of hyperphosphorylated tau and caspases in the brainstem of Alzheimer’s disease patients - Maria Sen Mun Wai; Yong Liang; Chun Shi; Eric Y. P. Cho; Hsiang-fu Kung; David T. Yew (Biogerontology, 2009)

Advance and prospectus of seasonal prediction: assessment of the APCC/CliPAS 14-model ensemble retrospective seasonal prediction (1980–2004) - Bin Wang; June-Yi Lee; In-Sik Kang; J. Shukla; C.-K. Park; A. Kumar; J. Schemm; S. Cocke; J.-S. Kug; J.-J. Luo; T. Zhou; B. Wang; et al. (Climate Dynamics, 2009)

Previous pulmonary disease and family cancer history increase the risk of lung cancer among Hong Kong women - Xiao-Rong Wang; Ignatius T. S. Yu; Yuk Lan Chiu; Hong Qiu; Zhenming Fu; William Goggins; Joseph S. K. Au; Lap-Ah Tse; Tze-Wai Wong (Cancer Causes & Control, 2009)

A Semi-Analytical Solution for Large-Scale Injection-Induced Pressure Perturbation and Leakage in a Laterally Bounded Aquifer–Aquitard System - Quanlin Zhou; Jens T. Birkholzer; Chin-Fu Tsang (Transport in Porous Media, 2009)

Caspase-3 binds diverse P4 residues in peptides as revealed by crystallography and structural modeling - Bin Fang; Guoxing Fu; Johnson Agniswamy; Robert W. Harrison; Irene T. Weber (Apoptosis, 2009)

Proteomic analysis of early germs with high-oil and normal inbred lines in maize - Zhanji Liu; Xiaohong Yang; Yang Fu; Yirong Zhang; Jianbin Yan; Tongming Song; T. Rocheford; Jiansheng Li (Molecular Biology Reports, 2009)

Lipid rafts play an important role in the vesicular stomatitis virus life cycle - W. Wang; Y. J. Fu; Y. G. Zu; N. Wu; J. Reichling; T. Efferth (Archives of Virology, 2009)

Genetic Diversity of Canadian and Exotic Potato Germplasm Revealed by Simple Sequence Repeat Markers - Yong-Bi Fu; Gregory W. Peterson; Ken W. Richards; T. Richard Tarn; Jane E. Percy (American Journal of Potato Research, 2009)

Predictability of South American low‐level jet using QuikSCAT ocean surface wind - H. Wang; R. Fu; J. K. Schemm; W. Tang; W. T. Liu (International Journal of Remote Sensing, 2008)

Structural basis for executioner caspase recognition of P5 position in substrates - Guoxing Fu; Alexander A. Chumanevich; Johnson Agniswamy; Bin Fang; Robert W. Harrison; Irene T. Weber (Apoptosis, 2008)

Interaction of magma with sedimentary wall rock and magnetite ore genesis in the Panzhihua mafic intrusion, SW China - Clément Ganino; Nicholas T. Arndt; Mei-Fu Zhou; Fabrice Gaillard; Catherine Chauvel (Mineralium Deposita, 2008)

Treatment with proteasome inhibitor bortezomib enhances antigen-specific CD8+ T-cell-mediated antitumor immunity induced by DNA vaccination - Chih-Wen Tseng; Archana Monie; Chao-Yi Wu; Bruce Huang; Mei-Cheng Wang; Chien-Fu Hung; T.-C. Wu (Journal of Molecular Medicine, 2008)

Ti-in-zircon thermometry: applications and limitations - Bin Fu; F. Zeb Page; Aaron J. Cavosie; John Fournelle; Noriko T. Kita; Jade Star Lackey; Simon A. Wilde; John W. Valley (Contributions to Mineralogy and Petrology, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Complete nucleotide sequences and genome characterization of double-stranded RNA 1 and RNA 2 in the Raphanus sativus-root cv. Yipinghong - L. Chen; J. S. Chen; L. Liu; X. Yu; S. Yu; T. Z. Fu; W. H. Liu (Archives of Virology, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Segmental nerve conduction velocity in vibration-exposed shipyard workers - M. Cherniack; A. J. Brammer; R. Lundstrom; J. Meyer; T. F. Morse; G. Nealy; T. Nilsson; D. Peterson; E. Toppilla; N. Warren; R. W. Fu; H. Bruneau (International Archives of Occupational and Environmental Health, 2004)

Mercury removal, methylmercury formation, and sulfate-reducing bacteria profiles in wetland mesocosms - Jeffrey K King; S.Michele Harmon; Theresa T Fu; John B Gladden (Chemosphere, 2002)

Sequence analysis of the S gene of recombinant MHV-2/A59 coronaviruses reveals three candidate mutations associated with demyelination and hepatitis - Jayasri Das Sarma, Li Fu, Susan T. Hingley, (Journal of NeuroVirology, 2001)

Mobility of components in metasomatic transformation and partial melting of gneisses: an example from Sri Lanka - L. L. Perchuk; O. G. Safonov; T. V. Gerya; B. Fu; D. E. Harlov (Contributions to Mineralogy and Petrology, 2000)

Analysis of mitochondrial DNA of an endangered beech species, Fagus hayatae Palibin ex Hayata - Sumie Kato; Takayoshi Koike; Thomas T. Lei; Chang-Fu Hsieh; Kunihiko Ueda; Tetsuo Mikami (New Forests, 2000)

Studies on somaclonal variation in Phalaenopsis - W. H. Chen; T. M. Chen; Y. M. Fu; R. M. Hsieh; W. S. Chen (Plant Cell Reports, 1998)

Heterogeneous cellular expression of creatine kinase isoenzyme during normal rat heart development - Russell T. Dowell; May C. Fu (Molecular and Cellular Biochemistry, 1998)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)